Achieving high gravimetric energy density for flexible lithium-ion batteries facilitated by core–double-shell electrodes. Issue 7 (11th May 2018) - Balogun, Muhammad-Sadeeq; Yang, Hao; Luo, Yang; Qiu, Weitao; Huang, Yongchao; Liu, Zhao-Qing; Tong, Yexiang
Abstract : Core–double-shell electrodes were designed to achieve flexible LIBs with an applicable energy density of 314 mA h g −1 (based on the device weight). Abstract : Flexible lithium-ion batteries (FLIBs) potentially offer lithium-ion battery energy density required for the production of flexible electronics. The design of FLIBs depends not only on the electrode materials but also on the entire weight of the battery device. However, low capacity contribution from the flexible substrate and poor interactions between the flexible substrate and active electrode materials lead to low capacity, representing low energy density. Herein, we concentrated on designing a flexible substrate (carbon cloth, CC), improving its conductivity and surface area to deliver high capacity, and further coating porous NiCo2 O4 nanowires on it to achieve a monolithic anode for high-gravimetric energy density FLIBs. Theoretical and in situ analyses were used to investigate Li-ion pathways and capacity contribution of the flexible substrate, respectively. In this regard, a 39.0 cm 2 all-flexible lithium-ion battery (with an entire weight of 281 mg) with high gravimetric energy density (314 W h kg −1 ), excellent flexibility, and good storage performance is attained, and it exhibits potential application for future flexible energy storage devices.